2015
DOI: 10.1186/s12966-015-0304-3
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined effects of physical activity and body mass index on the development of Type 2 Diabetes – a meta-analysis of 9 prospective cohort studies

Abstract: BackgroundThe aim of this harmonized meta-analysis was to examine the independent and combined effects of physical activity and BMI on the incidence of type 2 diabetes.MethodsOur systematic literature review in 2011 identified 127 potentially relevant prospective studies of which 9 fulfilled the inclusion criteria (total N = 117,878, 56.2 % female, mean age = 50.0 years, range = 25–65 years). Measures of baseline physical activity (low, intermediate, high), BMI-category [BMI < 18.4 (underweight), 18.5–24.9 (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 24 publications
1
40
0
1
Order By: Relevance
“…Physical activity has been associated with reduced risk of T2D in different populations [5][6][7][8][9][10][11][12][13][14][15][16], and the World Health Organization (WHO) recommends at least 150 min per week of moderate physical activity for health benefits [17]. Although many studies have demonstrated this inverse relationship between physical activity and risk of T2D, they have applied different metrics in quantifying physical activity and also used different domains (e.g., occupational, leisure-time, domestic and commuting), dimensions (e.g., type, rate, intensity and duration) and different modes of assessment, either quantitative or qualitative or a combination of both [10,16,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been associated with reduced risk of T2D in different populations [5][6][7][8][9][10][11][12][13][14][15][16], and the World Health Organization (WHO) recommends at least 150 min per week of moderate physical activity for health benefits [17]. Although many studies have demonstrated this inverse relationship between physical activity and risk of T2D, they have applied different metrics in quantifying physical activity and also used different domains (e.g., occupational, leisure-time, domestic and commuting), dimensions (e.g., type, rate, intensity and duration) and different modes of assessment, either quantitative or qualitative or a combination of both [10,16,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…La relación entre diabetes y obesidad/sobrepeso esta ya bien establecida por estudios anteriores; como el de Cloostermans et al (29) , HR: 7.4 (IC95% 3,47-15,89 e Hyppönen et al (30) , RR: 22,9 (IC 95%12-42). Así, las relaciones encontradas en estudios anteriores son mucho más contundentes en comparación con este estudio, lo que podría ser explicado por el tipo de selección de los pacientes (por conveniencia) y que, en su mayoría, las personas que acuden a los servicios de medicina complementaria ya poseen enfermedades crónicas establecidas y, probablemente, en tratamiento (17,23) , lo que hace que sea más probable encontrar obesidad que sobrepeso.…”
Section: Discussionunclassified
“…Type 2 diabetes mellitus (T2DM) is also a potentially modifiable risk factor for dementia [5], with estimates that nearly 200,000 cases of dementia could be prevented if there was a 25% reduction in T2DM [6]. Importantly, physical inactivity is one of the main causes of T2DM [7]. It has been well documented that regular exercise plays a major role in its prevention and management [8].…”
Section: Introductionmentioning
confidence: 99%